Development of a rapid detection technology system for noxious plants based on a novel isothermal amplification technique - Zhang, Ting; Xu, Han; Liu, Mengdi; Zhang, Wei (Frontiers in Plant Science, 2025)
Noxious plants pose a significant threat to human and livestock health, as well as to the safety of agricultural and forestry ecosystems. Accurate and rapid identification of these plants is crucial for risk prevention. This paper explores for the first time the development and application of a rapid detection technology for noxious plants based on a novel isothermal amplification technique. We targeted the seeds, leaves, and grain impurities of four major noxious weeds: Amaranthus palmeri, the A.tuberculatus complex, Rhaponticum repens, and Euphrosyne xanthiifolia, we designed and screened primers and probes suitable for this isothermal amplification method, determined their limit of detection, optimized the genomic DNA extraction methods, and verified the method. We developed genomic DNA extraction methods for single tissue components of plant seeds and leaves, as well as for mixed tissue components. Ultimately, we established standardized detection protocols for different tissue forms of each species, significantly enhancing detection efficiency. This study enables the detection positive samples in seeds or leaves within 10 to 15 minutes and positive samples from mixtures within 12 to 18 minutes. The entire process, from sample collection, genomic DNA preparation to reaction completion, takes approximately 35 minutes. This detection technology, which marks the first development of an isothermal amplification-based method for noxious plants, meets the needs for on-site rapid testing, aiding in the timely identification of risks and the implementation of corresponding prevention and control measures.